2015
DOI: 10.2166/wst.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat adsorption on NaX and Al-MCM-41

Abstract: The aim of this work is to determine paraquat adsorption capacity of zeolite NaX and Al-MCM-41. All adsorbents were synthesized by hydrothermal method using rice husk silica. For Al-MCM-41, aluminum (Al) was added to the synthesis gel of MCM-41 with Al content of 10, 15, 20 and 25 wt%. The faujasite framework type of NaX and mesoporous characteristic of Al-MCM-41 were confirmed by X-ray diffraction. Surface area of all adsorbents determined by N2 adsorption-desorption analysis was higher than 650 m2/g. Al cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…XRD patterns of NaX, NaY, PQX, and PQY are shown in Figure 2. Main peaks of PQX and PQY were similar to those of the bare zeolites (Rongchapo et al, 2013(Rongchapo et al, , 2015. XRD results indicated that paraquat adsorption did not change the zeolite structure.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…XRD patterns of NaX, NaY, PQX, and PQY are shown in Figure 2. Main peaks of PQX and PQY were similar to those of the bare zeolites (Rongchapo et al, 2013(Rongchapo et al, , 2015. XRD results indicated that paraquat adsorption did not change the zeolite structure.…”
Section: Resultsmentioning
confidence: 67%
“…Each supercage has a diameter of 1.3 nm and four open windows with a diameter of 0.74 nm (Guisnet and Gilson, 2002). The Si/Al ratios of NaX and NaY from our works are 1.2 and 2.2, respectively (Rongchapo et al, 2013(Rongchapo et al, , 2015. The presence of an Al atom in the zeolite framework generates a negative charge which requires a charge balancing cation.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…For this sample, the isotherm exhibits an H4 hysteresis loop. This isotherm is of the type I because it presents a quasi-horizontal plate and is characteristic of a microporous material (Rongchapo et al, 2015, Rongchapo et al, 2013, Rongchapo et al, 2018. In the specific surfaces area study, the parameters such as grain size and the degree of crystallization of the samples had a great influence on the meso-structure of the samples.…”
Section: N 2 Adsorption-desorption Isotherm and Porositymentioning
confidence: 99%